Lipin deactivation after acetaminophen overdose causes phosphatidic acid accumulation in liver and plasma in mice and humans and enhances liver regeneration. (May 2018) - Lutkewitte, Andrew J.; Schweitzer, George G.; Kennon-McGill, Stefanie; Clemens, Melissa M.; James, Laura P.; Jaeschke, Hartmut; Finck, Brian N.; McGill, Mitchell R.
Highlights: Phosphatidic acid increases in liver and circulation in mice after APAP overdose. Phosphatidic acid increases in circulation of humans with APAP hepatotoxicity. Reducing phosphatidic acid content in the liver blunts liver regeneration. Phosphatidic acid may affect liver regeneration through mTOR signaling.